Exploring Efficacy - Maryam, Rini; Irianto, Sulistyowati (University of Jember, 2023)
The rising global divorce rate is reshaping the landscape of family dispute resolution, moving away from the adversarial or litigation system toward an alternative dispute resolution known as mediation. This global trend is also observed in Indonesia where the Supreme Court has mandated the use of mediation in civil cases.